ANALISIS PERLINDUNGAN MEREK DAGANG TERHADAP SENGKETA NEGARA ISLE OF MAN DAN WEN KEN DRUG CO. PTE LTD - Riska Luneto; Aldilla Dika (UIN ALAUDDIN MAKASSAR, 2020)
Protection of trademarks (goods / services) is one of the important things for every inventor. The success of the WTO as an organization that oversees cooperation in the field of trade has an important role in the struggle that was resolved in the field of trade, in accordance with the agreement in the TRIPs which discussed Intellectual Property that was sponsored both nationally and internationally. The damaged trademark case by the Wen Ken Group Company later became an example of violation of the agreement, when the trademark product / service that was registered did not conflict with the logo, symbol or symbol of an ideology or the State. The resolution of this dispute is then still a polemic in Indonesia because the decisions made are not in accordance with the provisions in force, so they are approved by the WTO. Keywords: Intellectual Property Rights, WTO, TRIPs, Trademarks, Disputes